Control of a team of mobile robots based on non-cooperative equilibria with partial coordination - Skrzypczyk, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski)
In this work we present an application of the concept of non-cooperative game equilibria to the design of a collision free movement of a team of mobile robots in a dynamic environment. We propose the solution to the problem of feasible control synthesis, based on a partially centralized sensory system.
Keywords: multi-robot systems; motion planning; game theory